2013
DOI: 10.1109/tbme.2012.2212278
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Method for Personalized and Cost-Effective Detection of Alzheimer's Disease

Abstract: Diagnosis of Alzheimer's disease (AD) is often difficult, especially early in the disease process at the stage of mild cognitive impairment (MCI). Yet, it is at this stage that treatment is most likely to be effective, so there would be great advantages in improving the diagnosis process. We describe and test a machine learning approach for personalized and cost-effective diagnosis of AD. It uses locally weighted learning to tailor a classifier model to each patient and computes the sequence of biomarkers most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 13 publications
1
54
0
Order By: Relevance
“…Using their framework, a classification accuracy of 89.0% was obtained for HC versus AD and delineated a set of brain regions which were in agreement with previous clinical studies [76]. Recently, Escudero [77] proposed a more conventional ML approach for the identification of biomarkers for AD. Using a subset of the ADNI dataset, a comparable classification accuracy of 84.9% for HC versus AD was obtained.…”
Section: Hybrid Mechanistic Models and MLsupporting
confidence: 77%
“…Using their framework, a classification accuracy of 89.0% was obtained for HC versus AD and delineated a set of brain regions which were in agreement with previous clinical studies [76]. Recently, Escudero [77] proposed a more conventional ML approach for the identification of biomarkers for AD. Using a subset of the ADNI dataset, a comparable classification accuracy of 84.9% for HC versus AD was obtained.…”
Section: Hybrid Mechanistic Models and MLsupporting
confidence: 77%
“…In general, these methodological approaches underlie the foundation for implementation of personalized medicine, which could potentially revolutionize the way we diagnose and treat disease. Although the conceptual framework of personalized biomarkers for disease detection has only been recently advanced, it is rapidly gaining traction (40-42). For example, a recent study leveraged massive parallel sequencing to develop personalized biomarkers capable of identifying translocations in solid tumors (43).…”
Section: Discussionmentioning
confidence: 99%
“…Today’s health care environment requires biomarker tests that are maximally informative but minimally expensive. Escudero et al [420] proposed an approach to minimize the number of biomarkers required for diagnosis. This personalized and iterative approach initially attempts to classify the patient by comparison of available variables with data from a pool of local diagnosed patients.…”
Section: Methods Papersmentioning
confidence: 99%
“…The PredictAD appears capable of beneficially combining data from different modalities and therefore may prove a useful adjunct for decision support in a clinical environment. The study of Escudero et al [420] addressed cost-effectiveness of biomarker-based diagnosis. They found that when the number of biomarkers was minimized, classification accuracies were comparable to methods that include all biomarkers.…”
Section: Studies Of the Adni Cohortmentioning
confidence: 99%